The effect of bony morphology on anterior cruciate ligament injury and surgery - Janina Kaarre; Gillian Ahrendt; Joseph D. Giusto; Emre Anıl Özbek; Nicholas A. Apseloff; Volker Musah (Acta Orthopaedica et Traumatologica Turcica)
The exploration of underlying biological risk factors for anterior cruciate ligament (ACL) injury has generated a substantial body of literature describing the role of bony morphology of the knee. Morphological risk factors, such as poor tibiofemoral joint congruity, a narrow femoral intercondylar notch, and an increased posterior tibial slope (PTS), have been implicated in contributing to knee instability and biomechanical abnormalities. Additionally, investigations into sex-specific differences in bony morphology have unveiled distinct risk profiles for males and females. In light of these findings, surgical considerations for individuals with high-risk bony morphology have been developed. Procedures like anterior closing wedge high tibial osteotomy, aiming to address increased PTS, and lateral extra-articular tenodesis for patients with specific risk factors, have been established. The aim of this review is to provide an overview of the current evidence describing the relationship between bony morphology and ACL injury. Moreover, this review aims to discuss the surgical management and outcomes concerning patients exhibiting high-risk anatomic features